(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Introduction: Interprofessional education is considered to be an innovative and useful concept to accelerate the effort of transforming health professional education under health systems perspective. Generally Interprofessional Education (IPE) occurs when two or more professionals belong to different professional groups learn together through mutual interaction with the purpose to improve collaboration and the quality of care. The key for IPE is that the learning must be interactive. It is an important step in advancing health professional education for many years and has been endorsed by the Institute of Medicine as a mechanism to improve the overall quality of health care. Methods: Realizing the importance of IPE, a quasi experimental study was undertaken and conducted in Bangladesh in May 2014. Sample size was 32 out of which 15 teachers (Such as Professor, Associate Professor, Assistant Professor, Lecturer and Instructor) and 17 students of medical, dental, nursing, medical technology and allied health science institutes. All the participants voluntarily attended 5 sessions on basic concept on IPE, role delineation, communication, teamwork & team building and patient centered care followed by group work and group activities within three consecutive days. After those 5 sessions, views of the participants were sought through self administered structured questionnaire after data entry and analysis. Results: According to the study, 100% participants viewed that medical, dental, nursing, and medical technologists should have few common sessions in their student life while about 90.7% respondents opined that those sessions will develop positive relationship among them, which will help to feel and honor each others professional responsibilities viewed by all the respondents. It was also revealed that 96.9% respondents viewed that IPE sessions in student life will help to reduce silos in professional life. Better team work among doctors, nurses and medical technologists will ensure patient centered better health care was viewed by 100% respondents. Study recommended introducing IPE in Bangladesh to foster patient centered health care. Conclusion and Recommendation: The study concluded with recommendation that specific sessions for IPE should be incorporate in the under graduate education curriculum of the health professionals during their academic period and also during in- service period at workplace as part of their professional development to promote quality of care. Chatt Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 3-7